Earthquakes and economic growth - Peter Simonsen Fisker (Institute for Advanced Development Studies (INESAD), 2012)
This study explores the economic consequences of earthquakes. In particular, it is investigated how exposure to earthquakes affects economic growth both across and within countries. The key result of the empirical analysis is that while there are no observable effects at the country level, earthquake exposure significantly decreases 5-year economic growth at the local level. Areas at lower stages of economic development suffer harder in terms of economic growth than richer areas. In addition, the analysis proposes an explanation to the paradox that there is a pronounced negative effect at the regional level while no effect appears at the country level. To this end, the effects of earthquake exposure is investigated not only for the impact zones, but also for areas with an average distance to the epicenter of around 100 km. The results indicate that the decrease in production in one part of a country is (partially) off-set by an increase in production in the surrounding regions.
Keywords: O11; O49; R11; R12; 330; Economic growth; natural disasters; spatial distribution; Erdbeben; Wirtschaftswachstum; Räumliche Verteilung